2021
DOI: 10.1080/0144235x.2021.1918498
|View full text |Cite
|
Sign up to set email alerts
|

Physics and chemistry on the surface of cosmic dust grains: a laboratory view

Abstract: Dust grains play a central role in the physics and chemistry of cosmic environments. They influence the optical and thermal properties of the medium due to their interaction with stellar radiation; provide surfaces for the chemical reactions that are responsible for the synthesis of a significant fraction of key astronomical molecules; and they are building blocks of pebbles, comets, asteroids, planetesimals, and planets. In this paper, we review experimental studies of physical and chemical processes, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 350 publications
(384 reference statements)
0
26
0
Order By: Relevance
“…A fraction of the volatile ices remained trapped in the water ice and co-desorbed at higher temperatures of when the water ice sublimed. However, icy pebbles in the solar nebula might have gradually lost their volatile content over thousands of years and became more volatile-poor compared to the results of the TPD experiments, which were conducted over short timescales (hours–days) [ 63 , 72 ]. Another TPD experiment showed that some of the formaldehyde polymerizes in reaction with water to polyoxymethylene and therefore did not co-desorb with water at high temperatures [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…A fraction of the volatile ices remained trapped in the water ice and co-desorbed at higher temperatures of when the water ice sublimed. However, icy pebbles in the solar nebula might have gradually lost their volatile content over thousands of years and became more volatile-poor compared to the results of the TPD experiments, which were conducted over short timescales (hours–days) [ 63 , 72 ]. Another TPD experiment showed that some of the formaldehyde polymerizes in reaction with water to polyoxymethylene and therefore did not co-desorb with water at high temperatures [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…One has to keep in mind that in this study, it was assumed that the volatile ices are able to leave the water ice matrix freely. In the temperature programmed desorption (TPD) experiments, a fraction of these volatile ices remains trapped in the water ice and co-desorbs with it at higher temperatures of T 150 K. However, this trapping could be explained by the short timescales (hours-days) employed in these experiments, while icy pebbles in the solar nebula could have been gradually losing their volatile content over thousands of years, becoming more volatile-poor compared to the TPD results (Cuppen et al 2017;Potapov & McCoustra 2021). Indeed, the relatively efficient diffusion rates for the volatile ices such as CO, formaldehyde, and CO 2 at T 90 K were measured experimentally or predicted via molecular dynamics calculations (Ghesquière et al 2015, and references therein).…”
Section: Initial Concentrations Of Reactantsmentioning
confidence: 96%
“…Hama & Watanabe 2013;Zamirri et al 2018). Several hypothesis have been suggested to explain the absence of the OH dangling signature (Oba et al 2009;Palumbo 2006;Palumbo et al 2010), so that, at the end, there is consensus in the community that interstellar water ices are amorphous and porous in nature, even though many details are missing and we do not have a precise picture of the degree of porosity (e.g., Hama & Watanabe 2013;Isokoski et al 2014;Potapov & McCoustra 2021).…”
Section: Ice Modelmentioning
confidence: 97%
“…Many laboratory studies have been carried out to characterize the possible porosity of the interstellar ices. Typically, laboratory experiments produce porous ices of different densities by condensation of water vapor, even though they probably do not reproduce the interstellar water ice, in which water is believed to form in situ by hydrogenation reactions of frozen O, O 2 and O 3 (e.g., Dulieu et al 2010;Hama & Watanabe 2013;He & Vidali 2014;Potapov & McCoustra 2021). In general, porous ices are detected in laboratory via the infrared (IR) signature of A9, page 3 of 14 A&A 655, A9 (2021) dangling OH groups, which are, however, missing in interstellar samples (Bar-Nun et al 1987;Keane et al 2001), (see also the discussion in e.g.…”
Section: Ice Modelmentioning
confidence: 99%
See 1 more Smart Citation